Interações medicamentosas entre psicofármacos utilizados por pessoas com dependência química - Nascimento, Diego Zapelini do (2019)
Background: Using psychiatric drugs to treat drug dependence and its comorbidities is very common. Objective: The aimed of this study was to analyze the interactions between prescribed drugs for patients treated at a specialized mental health care center for drug addicts from 2010 to 2018 located in southern Brazil. Methods: A cross-sectional study was conducted on secondary data collected. We reviewed the medical records of patients aged 18 years or older who took psychotropic drugs and had any type of substance dependence. The analysis of psychotropic drug interactions was conducted in three databases: Medscape, Drug Interactions Checker, and Micromedex. The collected data were entered into the EpiData v.3.1 software. Statistical analysis was performed by using the IBM SPSS v.21 statistics software The Pearson‟s Chi-square test was used to test significant associations between each independent variable and the outcome studied, adjusted for potential confounding variables, using modified Poisson regression models. A P-value < 0.05 was considered statistically significant. Results: We included 1,022 of the 2,322 patients attending the care center during the study period. Psychotropic drug interactions were found in 779 (76.4%) study participants, and they presented 2,292 (100%) interactions, out of which 136 (6.0%) had minor clinical risk, 537 (23.4%) had moderate risk, and 1,619 (70.6%) had major risk for the patient, totaling 172 incompatible combinations between two psychotropic drugs. Of the total number of interactions, 128 were pharmacokinetic and 44 were pharmacodynamic. Among the 1,020 participants, 515 (50.5%) were dependent on alcohol, 310 (30.4%) were dependent on tobacco, and 238 (46.2%) were dependent on both drugs. We found 1,099 (215.5%) interactions between psychoactive drugs and alcohol and 160 (51.6%) interactions between psychoactive drugs and tobacco. There was an association between advanced age and alcohol dependence (p <0.001). Conclusion: The high number of psychotropic drug interactions is a serious public health issue. Psychopharmacological treatment should be carefully addressed to be safe for the patient.